Exfoliation of BN nanosheets for toughening SiO2f/SiO2 composites - Neo, Pitrie Wen Wei (2016)
Silica composites have been found to exhibit favourable properties in both high temperature and wave transparent applications. However, pure silica composites also undergo very brittle failure and techniques to improve their toughness has seen limited success. This project investigates the optimal processing parameters of the exfoliation of BN nanosheets using ball milling and ultrasonic probing methods, as well as its effect on the flexural properties and toughness mechanisms when incorporated in SiO2f/SiO2 composites. The starting material used h-BN to be processed into nanosheets while the composite was prepared with quartz matrix embedded into quartz layers of simple 2D weave fibres. It was found that after 16 hours of ultrasonication proceeding the ball milling process of 300 rpm for 15 hours, the size remained in the range of 200-250 nm. Four SiO2f/SiO2 composites were prepared with 1, 2 and 4 layers of BN coatings as interfaces between fibre and matrix, including one control sample without interface. Flexural testing was conducted to gauge the toughness based on the nature of the flexural stress-strain curves. The results show positive results as the BN nanosheets displayed signs of improving the toughening mechanism in demonstrating pseudo-plasticity effect as BN is applied. There was a general decreasing trend in average flexural yield strength and flexural modulus as more BN interface is applied, while the flexural strain at 50% yield strength increased. The data shows the effectiveness of the BN nanosheets in improving the toughness. Overall, the samples with 2-layer BN show a good pseudo-plasticity with acceptable flexural strength of ~40 MPa as compared to ~50 MPa in the control sample. The relatively high flexural strength together with its favourable toughening effect on the composite makes 2 layers of BN the optimal condition in this study. The fracture surfaces as observed in SEM analysis show increasing fibre pull-out length from ~30µm to 500-2000 µm. This evidence show increasing toughening mechanism due to more absorption of fracture energy as the number of layers of interfacial layers increased. Also, the residual matrix surrounding the fibres decrease with more coatings, proving the interfacial bonding between the fibre and matrix weakens as coating increases. The study achieved in both the exfoliation technique of synthesising BN nanosheets and its toughening effect, which paves the way into further studies to enable silica composites in real life applications.